Pregnancy-associated changes of peroxisome proliferator-activated receptor delta (PPARD) and cytochrome P450 family 21 subfamily A member 2 (CYP21A2) expression in the bovine corpus luteum - Ryosuke SAKUMOTO; Ken-Go HAYASHI; Misa HOSOE; Kosuke IGA; Keiichiro KIZAKI (The Society for Reproduction and Development, 2020)
We investigated gene expression profiles of the corpus luteum (CL) at the time of maternal recognition to evaluate the functional changes of the CL during early pregnancy in cows and help improve reproductive efficiency and avoid defective fetuses. Microarray analyses using a 15 K bovine oligo DNA microarray detected 30 differentially expressed genes and 266 differentially expressed genes (e.g., PPARD and CYP21A2) in the CL on pregnancy days 15 (P15) and 18 (P18), respectively, compared with the CL on day 15 (NP15) of non-pregnancy (n = 4 for each group). PPARD expression was the highest while the CYP21A2 expression was the lowest in P15 and P18 compared with that of NP15. These microarray results were validated by quantitative real-time PCR analysis. The addition of interferon-τ and supernatants derived from homogenized fetal trophoblast increased ISG15 and MX1 expressions in the cultured luteal tissue (P < 0.01), but did not affect PPARD and CYP21A2 expressions. PPARD expression in the luteal tissue was stimulated (P < 0.05) by GW0742, known as a selective PPARD agonist, and PPARD ligands (i.e., arachidonic, linoleic and linolenic acids). In contrast, CYP21A2 mRNA expression was not affected by both agonist and ligands. The concentration of prostaglandin (PG) E2 and PGF2α decreased after GW0742 stimulation and increased after arachidonic acid stimulation (P < 0.05). The addition of GW0742 and arachidonic acid increased progesterone (P4) concentration. Collectively, these findings suggest that high expression levels of PPARD and low expression levels of CYP21A2 in the CL during early pregnancy may support P4 production by bovine luteal cells.